Coworker networks from student jobs: A flying start at labor market entry? - Gökay Demir; Friederike Hertweck; Malte Sandner; Ipek Yükselen (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
This paper analyzes the impact of college students' coworker networks formed during student jobs on their labor market outcomes after graduation. For our analysis, we use novel data that links students' administrative university records with their pre- and post-graduation employment registry data and their coworker networks. Our empirical strategy exploits variation in the timing and duration of student jobs, controlling for a variety of individual and network characteristics, as well as firm-by-occupation fixed effects, eliminating potential selection bias arising from non-random entry into student jobs and networks. The results show that students who work alongside higher-earning coworkers during their student jobs earn higher wages in their first post-graduation employment. Two key mechanisms appear to drive this effect: (1) sorting into higher-paying firms after graduation, facilitated by coworker referrals, and (2) enhanced field-specific human capital through exposure to skilled colleagues. However, the initial wage advantage from higher-earning coworker networks diminishes over time as students with worse networks catch up. Our findings contribute to the understanding of how early career networks shape labor market outcomes and facilitate a smoother transition from higher education to graduate employment. – – In diesem Beitrag wird untersucht, wie sich die während Studentenjobs gebildeten Netzwerke auf den Arbeitsmarkteintritt von Studierenden nach Abschluss des Studiums auswirken. Für unsere Analyse verwenden wir eine neuartige Datenverknüpfung aus administrativen Universitätsdaten von Studierenden und Sozialversicherungsdaten der Studierenden sowie all ihrer Kolleginnen und Kollegen während der Studentenjobs. Unsere empirische Strategie nutzt Variationen im Zeitpunkt und in der Dauer der Studentenjobs und kontrolliert für eine Vielzahl von individuellen und Netzwerk-Charakteristika sowie für fixe Effekte zu Unternehmen und der Berufsgruppe, um mögliche Verzerrungen zu eliminieren, die sich aus der nicht zufälligen Selektion der Studierenden in bestimmte Studentenjobs und Netzwerke ergeben. Die Ergebnisse zeigen, dass Studierende, die während ihrer Studentenjobs mit besser verdienenden Kollegen zusammenarbeiten, in ihrer ersten Anstellung nach dem Studium höhere Löhne erzielen. Zwei Mechanismen scheinen für diesen Effekt verantwortlich zu sein: (1) Sortierung der Studierenden in besser zahlende Unternehmen nach dem Abschluss (unterstützt durch Empfehlungen ehemaliger Kolleginnen und Kollegen) und (2) verbessertes fachspezifisches Humankapital durch den Kontakt mit qualifizierten Kolleginnen und Kollegen während des Studentenjobs. Der anfängliche Lohnvorteil durch die besser verdienenden Netzwerke nimmt jedoch im Laufe der Zeit ab, da Studierende mit schlechteren Netzwerken aufholen.
Keywords: I23; J24; J31; 330; Coworker networks; student jobs; labor market entry; wages